2019
DOI: 10.1186/s12877-019-1257-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health-related quality of life between the Han and Yi ethnicity elderly in the Yi autonomous areas of Yunnan Province

Abstract: BackgroundThe purpose of this research was to assess the health-related quality of life (HRQOL) and functional abilities of Yi and Han elderly who resided in Yi Autonomous prefecture or Counties in Yunnan Province, as well as to compare their differences in HRQOL, functional abilities and other factors.MethodsA total of 1636 older subjects, which included 863 Han and 773 Yi, were recruited from 10 Yi Autonomous regions. Their HRQOL and functional capabilities were assessed by the MOS 36-Item Short Form Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Quick and effective assessment of ADL ability can help older adults enjoy the benefits of appropriate and effective care. It can also save on the cost of care and reduce the pressure on older adults’ care services[ 31 , 32 ]. Its use should therefore improve rehabilitation treatment, guide the continuity of care and ensure adequate social support and disability benefits for the older adults[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quick and effective assessment of ADL ability can help older adults enjoy the benefits of appropriate and effective care. It can also save on the cost of care and reduce the pressure on older adults’ care services[ 31 , 32 ]. Its use should therefore improve rehabilitation treatment, guide the continuity of care and ensure adequate social support and disability benefits for the older adults[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raggi et al also observed that there was no such correlation in the case of people from Finland (n=520) and Spain (n=2256) between life quality and the level of dexterity (IADL) [22]. The research done by Ran et al showed that the level of dexterity measured by the IADL scale was positively correlated with the level of life [11]. In the own research, the authors also showed that there were correlations between variables.…”
Section: Discussionmentioning
confidence: 92%
“…The results of the research done by Klompstra et al on a group of 238 people living at home with three or more chronic diseases, the average age was 82, also showed that a lower level of life quality was significantly connected to age [10]. The research done by Ran et al on a group of 1636 elderly people showed that old age conduces to a lower level of life quality [11]. In Raggi et al's research a negative correlation between life quality connected with health vs age was noted (p≤0,001) among Polish people, however, this correlation was not noted among people from Finland and Spain [22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, this pictorial-based Longshi scale would be of great signi cance especially for the elderly disabled with complications. Through the quick and effective assessment of ADL, the elderly can enjoy appropriate and effective care, and further save the cost of care, reduce the pressure on elderly care services [31,32]. Therefore, it would be bene t to improve the rehabilitation treatment, guide continuity of care and ensure adequate social support and disability bene ts for the elderly patients [27].…”
Section: Discussionmentioning
confidence: 99%